Cover image. Issue 4 (29th August 2018) - Unknown
Abstract : OspTx2a is a new potassium channel (KV )‐blocking peptide, identified from a transcriptomic and proteomic study of the sea anemone Oulactis sp. It belongs to the ShKT superfamily of peptides and proteins. Norton and co‐workers report the solid phase synthesis of OspTx2a. The synthetic peptide gave two peaks on HPLC, which had identical masses, the same disulfide bond connectivities, and very similar solution structures. NMR chemical shift and structural analyses suggest that the second species containsD ‐Cys at the C‐terminus rather thanL ‐Cys. Both peptides show activity against KV 1 channels. (doi:10.1002/pep2.24073 )